2014
DOI: 10.1021/jp412498t
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Active Molecular Wires Derived from Dinuclear Ferrocenyl/Ruthenium(II) Alkynyl Complexes: Covalent Attachment to Hydrogen-Terminated Silicon Surfaces

Abstract: International audienceAfter their brief characterization, a voltammetric study of the Fe(II)/Ru(II) heterobinuclear organometallic complexes [Fe]C≡C-1,4-(C6H4)C≡C[Ru]C≡C-1,4-(C6H4)C≡CH (2), FcC≡C[Ru]C≡C-1,4-(C6H4)C≡CH (3), and PhC≡C[Ru]C≡C-1,1′-Fc(C≡CH) (4) ([Fe] = Fe(κ2-dppe)(η5-C5Me5), [Ru] = trans-Ru(κ2-dppe)2; Fc = ferrocenyl; dppe =1,2-bis(diphenylphosphino)ethane) is reported in solution. These complexes which possess pendant ethynyl groups have then been grafted onto hydrogenated silicon surfaces using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 106 publications
2
45
0
Order By: Relevance
“…Therefore, for the present study we selected the B3LYP functional and the basis 1 to run the geometry optimizations and hessian calculations, while chose basis 2 to refine the calculated energy through single point calculations. The choice of B3LYP functional and LANL2DZ basis set as an adequate choice is further supported by several publications describing the behavior of various organometallic compounds including a phthalocyaninoclathrochelate …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, for the present study we selected the B3LYP functional and the basis 1 to run the geometry optimizations and hessian calculations, while chose basis 2 to refine the calculated energy through single point calculations. The choice of B3LYP functional and LANL2DZ basis set as an adequate choice is further supported by several publications describing the behavior of various organometallic compounds including a phthalocyaninoclathrochelate …”
Section: Resultsmentioning
confidence: 99%
“…The formation, isolation and characterisation of the vinylidene complexes [1]BF4 and mono-alkynyl complexes 2 allowed the sequence of events leading to the formation of trans-bis(alkynyl) complexes 3 vs. the η 3 -butenynyl complexes [4]BF4 to be followed by in situ 31 P{ 1 H} NMR spectroscopy. From a mixture of cis-RuCl2(dppm)2 TlBF4, HC≡CC6H4-4-R and 1,8-bis-dimethylaminonaphthalene in CH2Cl2 solutions, the mono-alkynyl complexes 2 (s, ca.…”
Section: Discussionmentioning
confidence: 99%
“…For cases when the R substituent is electron withdrawing ( Figure 5), 3 were ultimately formed without any appreciable byproducts. However, when the R substituent is electron donating (Figure 6), before complete conversion of 2 to 3, the η 3 -butenynyl complex [4] + is observed with four new 31 P{ 1 H} NMR resonances in a characteristic ABMX coupling pattern. 35 As the reaction proceeds, the product distribution shifts to give the η 3 -butenynyl species cleanly without any appreciable by-products, implying the intermediacy of 3 in the formation of [4] + .…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] For instance Grelaud et al recently reported the attachment of a dinuclear ferrocenyl/ruthenium(II) alkynyl redox-active side chain onto hydrogen-terminated silicon. 19 However, most of these synthesis efforts involve multistep synthesis processes of the complex side chains and some high-value (noble metal) materials to improve the resulting conductivity and stability. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 In contrast to the current experimental approaches for attaching metallocenes onto supports, our previous simulation study identified an extraordinarily strong direct immobilization of cyclopentadienyl-transition metal complexes (CpTM) onto B-doped nanocarbons (including carbon nanotubes (CNTs) and graphene supports).…”
Section: Introductionmentioning
confidence: 99%